Changes in shoulder range of motion following arthroscopic rotator cuff repair: a systematic review - Carla Antonacci; Umile Giuseppe Longo; Emiliano Schena; Mariajose Villa Corta; Greta Di Sabatino; Adriana Elvira Arab Orozco; Alessandro de Sire; Arianna Carnevale (BMC Musculoskeletal Disorders)
Abstract Rotator cuff (RC) tears are a leading global cause of pain and physical impairment, impacting patients' quality of life and daily activities. Surgical treatments are the recommended approach for patients with acute symptomatic RC tears that aim to restore shoulder movement function. Kinematic outcomes, following arthroscopic RC repair lack consensus, needing clarity on changes in shoulder kinematics. This study aims to report alterations in shoulder kinematics in patients with RC tear following arthroscopic repair, with a focus on evaluating changes in the range of Motion (ROM) during clinically relevant upper limb exercises. A systematic literature review was conducted utilizing PubMed, IEEE Xplore, and Web of Science databases until September 2023, resulting in the identification of 13 relevant articles. The results showed high heterogeneity among studies regarding patients’ population, type of RC tears, and experimental protocol. Different commercially available technologies were employed among the studies for monitoring the shoulder kinematics, but the goniometer appeared to be the most used device in this clinical setting. This review included studies assessing shoulder kinematics following arthroscopic RC repair during the execution of simple movements (e.g., forward/backward flexion, internal/external rotation, and abduction/adduction) and tasks related to activities of daily living. Although internal and external rotations were the most affected movements, studies demonstrated varied ROM recovery patterns post-surgery, characterized by initial slow improvement within the first three months followed by a progressive boost at six months post-surgery. This systematic review proves that ROM recovery post-arthroscopic surgery shows gradual improvement, with significant increases starting at 6 months and peaking at 12 months post-surgery, results that approach values seen in healthy subjects. However, several limitations, such as variability in patient characteristics, differences in monitoring systems, and the need for a standardized protocol, suggest the necessity for further research to optimize clinical practice and improve patient care.